Association between flavor composition and sensory profile in thermally processed mandarin juices by multidimensional gas chromatography and multivariate statistical analysis. (1st September 2023) - Cheng, Yujiao; Han, Leng; Huang, Linhua; Tan, Xiang; Wu, Houjiu; Li, Guijie
Graphical abstract: Highlights: Seventy-four volatiles were determined in fresh and heated mandarin juice. Heat processing enhanced the cook and off-flavor notes of mandarin juice. Various combinations of 4 sulfur volatiles generate off-notes including cook note. Ten odorant markers were identified based on both FD and OAV multivariate analysis. Abstract: Thermal pasteurization decreases the sensory quality of mandarin juice. Flavor composition was determined in four fresh-squeezed and heat-processed mandarin juice varieties using molecular sensory science approaches. The relationships between odorants and sensory profiles were analyzed, and markers for flavor deterioration were screened by multivariate statistical analysis. Seventy-four volatiles were identified, among which 36 odorants with flavor dilution factors ranging from 2 to 128 were detected by multidimensional gas chromatography-mass spectrometry/olfactometry (MDGC-MS/O) coupled with aroma extract dilution analysis (AEDA). Higher intensities of cooked and off-flavor notes were observed in the heated mandarin juice, which was related to the concentration changes of the methional, methanethiol, dimethyl sulfide, and carbon disulfide by partial least squares (PLS) analysis. Ten potential markers (methional, methanethiol, dimethyl sulfide, hydrogen sulfide, β -damascenone, camphene, trans - β -ionone, decanal, d -limonene, and α -pinene) were responsible for the sensory discrimination of fresh-squeezed and heated mandarin juices.